Removal of Reactive Yellow 4R Azo Dye from Synthetic Aqueous Solution by Alkali Hydrothermally Activated Fly Ash - Fadjari Lucia Nugroho; Deni Rusmaya; Angela Deviliana (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
Dye-containing wastewater affects the aesthetic quality, transparency and gas solubility of natural water bodies, hence colored wastewater must be treated before being discharged. Physical removal of dyes from wastewater can be achieved using activated carbon. However, this technique is expensive, so there is a need to find less expensive alternatives. A waste product generated from coal-fired plants known as fly ash is a sorbent that can be used to remove pollutants from solution. This study investigated the effectiveness of using alkali (NaOH) hydrothermally activated fly ash to remove Reactive Yellow 4R azo dye from synthetic aqueous solution. Na2O in alkali hydrothermally activated fly ash increases thirteen-fold. SEM observations revealed that the raw fly ash consisted of smooth round shaped particles, whereas the activated fly ash was composed of granular crystalline particles. Batch adsorption experiments of the dye at 25 °C showed that increasing the activated fly ash quantity (0.5 to 3.5 g) increased the removal efficiency from 30% to 39.3%. The Freundlich isotherm adsorption model best described the adsorption of Reactive Yellow 4R dye by alkali hydrothermally activated fly ash with KF = 1.49 x 10-21 mg/g. The dye adsorption kinetics by activated fly ash followed the Lagergren pseudo second order model, with calculated qe = 2.65 mg/g; k2 = 0.06 g/mg; and calculated h = 0.42 mg/g min‑1. Dye removal occurred primarily through surface adsorption and very little through intra-particle diffusion.